Budget impact analysis of a pilot polypharmacy clinic. Issue 4 (2nd April 2022) - Bennett, Frances; Barron, Andrew; Shah, Neha; Webb, David J; Sofat, Reecha
Abstract : Background/Aims: Inappropriate polypharmacy can lead to adverse events and increased healthcare costs. This study estimated the budget impact of providing a specialist onward referral service for patients with potentially problematic polypharmacy. Methods: A multidisciplinary team-led pilot polypharmacy clinic, dedicated to reviewing patients prescribed more than 10 different medications, was trialled in a secondary care setting. Potentially inappropriate prescribing was identified and addressed. Data from the pilot clinic regarding costs, direct savings and indirect savings were used to create budget impact models. Two service models were proposed: an outpatient model, based on the pilot clinic, and an integrated model, a theoretical integrated service collaborating with colleagues in primary care. Base case results and sensitivity analyses were calculated for both models. Results: Annual overall cost savings from the outpatient model and integrated model were estimated at £67 158 and £34 176 respectively. Both models were predicted to produce both direct and indirect savings from stopping unnecessary drugs and preventing hospital admissions for adverse drug reactions. Sensitivity analysis confirmed these results across all included variables except the number of medications stopped at review. Conclusions: Specialist onward referral services, dedicated to reviewing complex patients with high-risk polypharmacy, could offer significant cost savings, while also preventing adverse side effects and drug-related events.